Brief intervention and the Theory of Planned Behavior: a randomized controlled trial among adolescents - Gimenez, Paula Victoria (2023)
Brief Intervention (BI) is a successful tool for reducing adolescent drinking, although little is known about how it works to change behavior. Components of the Theory of Planned Behavior (TPB) predict alcohol consumption in this population; thus, modifying them through BI could be beneficial. This study aimed to determine if BI for alcohol drinking among adolescents affects the TPB components’, considering readiness to change. Participants were 102 Argentinean high school students (age M = 15.08, SD = 1.38, 85% male). We compared two groups: 1) evaluation about alcohol consumption, TPB’s components and readiness to change 2) same evaluation plus a BI. After three months, the BI group showed a significant reduction in intention (β =-1.21; p<.05) and perceived social norms (β =-2.79; p<.01). However, readiness to change did not predict any changes in TPB’s components. This study contributes to understanding BI’s mechanisms of change and closing the evidence gap from Latin America.